(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
Aeroponic systems have demonstrated their efficacy for seed potato production in greenhouses using sunlight or artificial light, achieving yields comparable or superior to traditional methods. However, the optimal light requirements, particularly with LED lights in aeroponic farming, remain understudied. This study aimed to determine the light compensation point (Ic) requiered for potato growth under LED lighting. The light compensation point is the irradiance where photosynthesis equals respiration, varying by species and environment. Selecting an appropriate light intensity is crucial for crop productivity and cost-efficiency. Limited research exists on potato cultivation under LED lighting, especially concerning plant photosynthetic rates. This study evaluated the effects of LEDs on potato plants, focusing on CO2 exchange and biomass production. Results indicated that blue light was the most efficient for CO2 absorption, with an Ic of 50 mol m? s?, while red light required 67 mol m? s?. White and mixed lights exhibited higher Ic values (84.6 and 108.5 mol m? s?, respectively). Plants exposed to blue light developed robust structures but had lower biomass compared to those under red light treatments, underscoring the need for further optimization of LED spectra in aeroponic farming systems.